2012
DOI: 10.2174/138161212801327310
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinases as Potential Targets for Novel Anti-Schistosomal Strategies

Abstract: Schistosome parasites are the causative pathogens of schistosomiasis (bilharzia), a disease of worldwide significance. In terms of patient numbers, schistosomiasis ranks second to malaria as a parasitosis affecting more than 200 million people of the tropics and subtropics. Since the 1970s Praziquantel (PZQ) is the drug of choice and nearly exclusively used for treatment. However, drug resistance is an increasing threat, particularly with respect to large-scale PZQ administration programs. Last decade´s resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 182 publications
(231 reference statements)
5
25
0
Order By: Relevance
“…This was confirmed by an independent approach recently, which reproduced similar phenotypes in vitro , although a first in vivo experiment failed [106]. Nonetheless, the data obtained in this study support the conclusion that Imatinib exerts broad negative effects on worm physiology substantiating the hypothesized role of PKs as potential targets [25], [28], [36], [42], [43]. In this respect it was encouraging to note that according to our microarray analysis also multidrug resistance (MDR) genes (Smp_089200, Smp_151290) were among the significantly down-regulated genes following Imatinib treatment.…”
Section: Discussionsupporting
confidence: 86%
“…This was confirmed by an independent approach recently, which reproduced similar phenotypes in vitro , although a first in vivo experiment failed [106]. Nonetheless, the data obtained in this study support the conclusion that Imatinib exerts broad negative effects on worm physiology substantiating the hypothesized role of PKs as potential targets [25], [28], [36], [42], [43]. In this respect it was encouraging to note that according to our microarray analysis also multidrug resistance (MDR) genes (Smp_089200, Smp_151290) were among the significantly down-regulated genes following Imatinib treatment.…”
Section: Discussionsupporting
confidence: 86%
“…They are involved in many biological processes such as cell growth, proliferation and differentiation. In schistosomes, PKs have been shown to play major roles in development and reproduction processes ( Beckmann et al, 2012; Dissous et al, 2014a ). Targeting of diverse PKs was shown to affect reproductive biology of parasites, as well as survival of adult worm and/or schistosomula in vitro , supporting the hypothesis that PK inhibitors are potential chemotherapeutics against schistosomiasis ( Dissous and Grevelding, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Their biochemical characteristics are well studied due to their importance in cancer, and a large variety of small molecules targeting selectively kinase activities is now commercially available and already used for human cancer therapy ( Johnson, 2009 ). In schistosomes, many studies have shown that PKs are implicated in essential functions at every stage of the parasite life cycle, and that these enzymes represent suitable anti-parasite drug targets ( Dissous et al, 2007, 2014a; Dissous and Grevelding, 2011; Beckmann et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…After perfusion, adult schistosomes were washed three times with M199 medium before being cultured in the same medium (Gibco; including glucose, sodium bicarbonate, 4-(2-hydroxyethyl)-1-piperazineethane sulfonic acid) supplemented with an antibiotic/antimycotic mixture (1%, Sigma) and new born calf serum (NCS) (10%, Sigma Aldrich) at 37°C and 5% CO 2 as described before ( Beckmann and Grevelding, 2010; Beckmann et al, 2012 ). For each experiment, 5–10 S. mansoni couples were kept per well in 6-well or 12-well plates with 2–3 ml culture medium per well.…”
Section: Methodsmentioning
confidence: 99%